Moxifloxacin : a new Fluoroquinolone for Respiratory Tract Infections - Wimolwattanapun, Suwat (Journal of Basic and Applied Pharmacology, 2015)
Moxifloxacin, an 8-methoxyquinolone, is a new forth generation fluoroquinolone launched recently. Its activity against Gram-positive bacteria is obviously better than most of the older· fluoroquinolones, while its activities against Gram-negative bacteria and atypical organisms such as mycoplasma, chlamydia and listeria remain high as other fluoroquinolones (MIC90 for most respiratory pathogens 0.06-0.25 mg/L). The increased coverage of Gram-positive pathogens especially S. pneumoniae and S. pyogenes, together with its excellent pharmacokinetic property (Cmax 2.5-5.0 mg/L, Tmax 1-4 h., Tl/2 11.4- 15.6 h. after 400 mg single oral dose) lending it to be used orally as single daily dose, make the drug valuable for ambulatory treatment of both upper and lower respiratory tract infections. Clinical studies of the drug on community-acquired pneumonia, acute exacerbation of chronic bronchitis and acute sinusitis have been convincing for its efficacy and safety. Furthermore, a recent study on acute exacerbation of chronic bronchitis demonstrated a more rapid resolution of fever and some respiratory symptoms achieved from moxifloxacin treatment compared to those achieved from macrolides. The recommended dose of the drug is 400 mg per oral once daily 5, 7 and 10 days for acute exacerbation of chronic bronchitis, acute sinusitis and community-acquired pneumonia respectively.